Exports in Mexico: an Analysis of Cointegration and Causality (1980-2012) - Miguel Heras Villanueva; Carlos Gómez Chiñas (Norteamérica)
This article analyzes the relationship between exports and output using econometric multivariate time series techniques (the Johansen cointegration test and Granger causality analysis). Using an error-correction model estimate, the authors show the long-term relationship between Mexico’s exports and gdp as well as the causality between these variables. This makes it possible to elucidate the kind of trade the country carries out, one of the causes of its low growth over the last three decades.